The Authority of Prosecutors to Seize Assets in Corruption Cases - Agung Pamungkas; Achmad Faisal; Anang Shophan Tornado (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Corruption is an extraordinary crime that not only causes massive state financial losses but also impedes national development. Efforts to eradicate corruption are insufficient if limited to the imprisonment of perpetrators; they must be accompanied by state asset recovery. The prosecutor, as the dominus litis in the criminal justice sistem, plays a central role in the process of seizing assets derived from corruption. This research aims to analyze the authority of prosecutors to seize assets in corruption cases, identify the obstacles encountered, and formulate solutions to optimize the exercise of this authority. The research method employed is normative juridical, utilizing a statutory approach and a case approach. The findings indicate that prosecutors have a strong legal basis for asset seizure, as stipulated in the Criminal Procedure Code (KUHAP), the Anti-Corruption Law, and other relevant regulations. However, in practice, prosecutors face various obstacles, both juridical, such as legal loopholes in the evidentiary process, and non-juridical, such as the complex modus operandi of perpetrators in concealing assets, slow inter-agency coordination, and challenges in tracing assets located abroad. Therefore, it is imperative to strengthen the regulatory framework through the enactment of the Asset Forfeiture Bill, enhance the capacity and integrity of prosecutors, and bolster international cooperation to maximize the recovery of state losses.